2021
DOI: 10.1007/s10643-021-01195-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Early Childhood Educator’s Perspectives and Practices in Nutrition and Physical Activity: A Qualitative Study

Abstract: Government guidelines for relaunching early childhood education and care (ECEC) programs during the COVID-19 pandemic have required the implementation of various practices to minimize the risk of infection transmission. These directives include recommendations regarding serving and handling food, shared spaces, and physical distancing which have a direct impact on the health and development of children in care. The purpose of this study was to explore early childhood educators’ perspectives on how COVID-19 gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 34 publications
3
54
2
Order By: Relevance
“…On the primary variable of interest, most studies (57 studies) reported a decrease in physical activity, both in duration and frequency of physical activity (see Table 1 ). Four studies identified an increase in physical activity [ 15 , 16 , 17 , 18 ], whereas six studies could detect no significant difference in physical activity behaviors before and during the pandemic [ 19 , 20 , 21 , 22 , 23 , 24 ]. Eight studies reported differentiated results with indoor and organized sports and physical activity decreasing, while non-organized and outdoor sports and physical activity increased [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the primary variable of interest, most studies (57 studies) reported a decrease in physical activity, both in duration and frequency of physical activity (see Table 1 ). Four studies identified an increase in physical activity [ 15 , 16 , 17 , 18 ], whereas six studies could detect no significant difference in physical activity behaviors before and during the pandemic [ 19 , 20 , 21 , 22 , 23 , 24 ]. Eight studies reported differentiated results with indoor and organized sports and physical activity decreasing, while non-organized and outdoor sports and physical activity increased [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that public recommendations for maintaining physical activity have so far been ineffective. If an increase has been detected, it occurred in outdoor play and unstructured activities [ 15 , 26 , 29 , 30 , 31 ] or related to lower levels of national restrictions [ 17 ]. The increase in outdoor activities depends strongly on the housing environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These guidelines drew attention to critical health practices and eating environments. In Alberta, changes in food provision for ECEC centers early in COVID-19 reopening contexts resulted in many parents providing food as many centers did not initially bring back cooks into programs [33]. In a previous qualitative study, educators noted a change in the quality and/or quantity of meals and snacks supplied by families [33].…”
Section: Covid-19 and Nutrition Environments In Ecec Settingmentioning
confidence: 99%
“…In Alberta, changes in food provision for ECEC centers early in COVID-19 reopening contexts resulted in many parents providing food as many centers did not initially bring back cooks into programs [33]. In a previous qualitative study, educators noted a change in the quality and/or quantity of meals and snacks supplied by families [33]. Financial challenges experienced by families were also identified as a possible reason for reduced nutritional quality or quantity as many families faced financial challenges, which possibly resulted in food insecurity [34].…”
Section: Covid-19 and Nutrition Environments In Ecec Settingmentioning
confidence: 99%